Acoustic emission assessment of interface cracking in thermal barrier coatings - Yang, L.; Zhong, Z.; Zhou, Y.; Zhu, W.; Zhang, Z.; Cai, C.; Lu, Chunsheng (Springer, 2016)
© 2015, The Chinese Society of Theoretical and Applied Mechanics; Institute of Mechanics, Chinese Academy of Sciences and Springer-Verlag Berlin Heidelberg.In this paper, acoustic emission (AE) and digital image correlation methods were applied to monitor interface cracking in thermal barrier coatings under compression. The interface failure process can be identified via its AE features, including buckling, delamination incubation and spallation. According to the Fourier transformation of AE signals, there are four different failure modes: surface vertical cracks, opening and sliding interface cracks, and substrate deformation. The characteristic frequency of AE signals from surface vertical cracks is 0.21 MHz, whilst that of the two types of interface cracks are 0.43 and 0.29 MHz, respectively. The energy released of the two types of interface cracks are 0.43 and 0.29 MHz, respectively. Based on the energy released from cracking and the AE signals, a relationship is established between the interface crack length and AE parameters, which is in good agreement with experimental results.